Effective Public Involvement Using Limited Resources - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 407: Effective Public Involvement Using Limited Resources explores information about staff and agency experiences in the application of successful and cost-effective strategies and implementation techniques used to engage the public in the development of transportation plans and projects. The report also examines unsuccessful strategies.
Keywords: Transportation and Infrastructure

Research on Women's Issues in Transportation, Volume 1: Conference Overview and Plenary Papers - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2006)
TRB's Conference Proceedings 35, Research on Women's Issues in Transportation, Volume 1: Conference Overview and Plenary Papers contains the conference summary, the four peer-reviewed overview papers presented by the topic leaders, and a list of conference participants from a November 18-20, 2004, conference held in Chicago, Illinois. The conference was designed to identify and explore additional research and data needed to inform transportation policy decisions that address women's mobility, safety, and security needs and to encourage research by young researchers. Volume 2 contains 22 full papers from the breakout and poster sessions and 9 abstracts of papers on subjects of particular interest to the committee that were selected for publication through the committee's peer review process.
Keywords: Transportation and Infrastructure

Practical Approaches for Involving Traditionally Underserved Populations in Transportation Decisionmaking - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 710: Practical Approaches for Involving Traditionally Underserved Populations in Transportation Decisionmaking highlights tools, techniques, and approaches for identifying and connecting with populations that have traditionally been underserved and underrepresented in transportation decisionmaking.
Keywords: Transportation and Infrastructure

Research on Women's Issues in Transportation - Volume 2: Technical Papers - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s Conference Proceedings 35: Research on Women’s Issues in Transportation – Volume 2: Technical Papers contains peer-reviewed breakout and poster papers and several abstracts of papers presented at the November 18–20, 2004, conference in Chicago, Illinois. The conference was designed to identify and explore additional research and data needed to inform transportation policy decisions that address women’s mobility, safety, and security needs and to encourage research by young researchers. Volume 1, which will be released this winter, will include the conference summary, the four peer-reviewed overview papers presented by the topic leaders, and a list of conference participants.
Keywords: Transportation and Infrastructure

Redesigning Transit Networks for the New Mobility Future - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Urban travel patterns are affected by many factors including changes in demography, land use, economics, technology, and mobility options. Public transportation must evolve to remain responsive.The TRB Transit Cooperative Research Program's TCRP Research Report 221: Redesigning Transit Networks for the New Mobility Future presents case studies and toolkits to plan and implement the redesign of bus networks in the United States.
Keywords: Transportation and Infrastructure

Women’s Issues in Transportation: Summary of the 4th International Conference, Volume 2: Technical Papers - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
Women’s Issues in Transportation: Summary of the 4th International Conference, Volume 2: Technical Papers includes 27 full peer-reviewed papers that were presented at the October 2009 conference. The conference highlighted the latest research on changing demographics that affect transportation planning, programming, and policy making, as well as the latest research on crash and injury prevention for different segments of the female population. Special attention was given to pregnant and elderly transportation users, efforts to better address and increase women’s personal security when using various modes of transportation, and the impacts of extreme events such as hurricanes and earthquakes on women’s mobility and that of those for whom they are responsible.TRB’s Conference Proceedings 46: Women’s Issues in Transportation, Volume 1: Conference Overview and Plenary Papers includes an overview of the October 2009 conference and six commissioned resource papers, including the two keynote presentations.
Keywords: Transportation and Infrastructure

Innovative Rural Transit Services - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s Transit Cooperative Research Program (TCRP) Synthesis 94: Innovative Rural Transit Services highlights transit and rural intercity bus service responses to changing rural community transportation needs. The report includes an emphasis on the innovative and/or entrepreneurial spirit, the innovator, and the conditions required for innovation.
Keywords: Transportation and Infrastructure